Cobalt-catalyzed ammonia borane dehydrogenation: Mechanistic insight and isolation of a cobalt hydride-amidoborane complex - Garcia Melchor, Max (My University, 2020)
A Co(I) complex featuring the electron-rich monoanionic bis(carbene) aryl pincer ligand (MesCCC) (MesCCC = bis(2,4,6-trimethylphenyl-benzimidazol-2-ylidene)phenyl), (MesCCC)Co-py (1), was found to catalytically dehydrogenate ammonia borane (NH3BH3, AB) in THF at 60 °C. This process releases 1.7 ± 0.1 equiv of H2 per AB with simultaneous formation of both soluble (borazine and polyborazylene) and insoluble (poly(aminoborane)) BN-containing species. To help elucidate the Co species present under the catalytic conditions, 1 was reacted with a stoichiometric amount of AB in THF at room temperature, yielding (MesCCC)CoH(NH2BH3) (2), the first characterized hydride-amidoborane complex of a late transition metal. This complex was characterized by multinuclear (1H, 11B, and 13C) NMR and IR spectroscopies as well as X-ray crystallography. Formation of 2 via N–H activation of AB across the Co(I) center of 1 was confirmed by the reaction of 1 with the deuterated isotopologues of AB and was supported computationally by means of density functional theory (DFT) calculations. Isolated 2 was shown to catalyze AB dehydrogenation, forming BN-containing products similar to 1, albeit at a slower rate. In both reactions starting with 1 or 2 as the catalyst, 2 is observed throughout the catalytic dehydrogenation of AB. DFT calculations revealed plausible pathways for the formation of aminoborane (NH2BH2) from 2, the generation of soluble BN-containing products, as well as the on-metal oligomerization of AB to produce the insoluble polymeric species. The complexes reported herein represent rare examples of homogeneous cobalt catalysts for the dehydrogenation of AB.
PUBLISHED